The Responsibilities of Influencers in Promoting Tie-Dye Motif Products Based on Copyright Law - Dwijayanthi, Putri Triari; Dharmawan, Ni Ketut Supasti (Susbtantive Justice International Journal of Law, 2020)
Tie-dye is known as a method of dyeing which results in a design on the fabric by which the fabric is collected and tied tightly with fibres, rope, or yarn, then dyed or coloured. The cloth is then processed into clothes, masks, and other accessories which can now be easily found in several online shops. This paper aims to identify, analyze, and elaborate on the legal protection of tie-dye motifs based on Indonesia Law Number 28 the Year 2014 concerning Copyright and the responsibilities of influencers who promote tie-dyed motif products. This is normative legal research with a statutory approach and a conceptual approach. The technique of tracing legal materials uses document study techniques and the analysis of studies uses qualitative analysis. The study shows that the tie-dye motif has been protected under Copyright law both nationally and internationally. Tie-dye motif as a form of continues to be developed with a high economic value has received clear protection under Indonesia Law Number 28 of 2014 concerning Copyright. The clear arrangement of tie-dyes is becoming increasingly important, especially when tie-dyes are used commercially. Regarding the Announcement of a copyrighted work, such as tie-dye products, the element of the uniqueness of form and originality are important points in copyright protection, so it is only natural for an influencer not to allow the sale and/or duplication of goods resulting from infringement of copyright and/or Related Right as regulated in Indonesia Copyright Law.